Genetics-Based Approach to Identify Novel Genes Regulated by the Aryl Hydrocarbon Receptor in Mouse Liver. (15th March 2021) - Jurgelewicz, Amanda; Dornbos, Peter; Warren, Melanie; Nault, Rance; Arkatkar, Anooj; Lin, Hui; Threadgill, David W; Zacharewski, Tim; LaPres, John J
Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor in the Per-Arnt-Sim superfamily of environmental sensors that is linked to several metabolic diseases, including nonalcoholic fatty liver disease. Much remains unknown regarding the impact of genetic variation in AHR-driven disease, as past studies have focused on a small number of inbred strains. Recently, the presence of a wide range of interindividual variability amongst humans was reported in response to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD), the prototypical ligand of the AHR. In this study, a panel of 14 diverse mouse strains was exposed to TCDD for 10 days to characterize the AHR-mediated response across genetic backgrounds. Responses to TCDD are heavily dependent on genetic background. Although mice carry 1 of 4 Ahr alleles known to impact the affinity to AHR-ligands, we observed significant intra-allelic variability suggesting the presence of novel genetic modifiers of AHR signaling. A regression-based approach was used to scan for genes regulated by the AHR and/or associated with TCDD-induced phenotypes. The approach identified 7 genes, 2 of which are novel, that are likely regulated by the AHR based on association with hepatic TCDD burden ( p ≤ .05). Finally, we identified 1 gene, Dio1, which was associated with change in percent body fat across the diverse set of strains ( p ≤ .05). Overall, the results in this study exemplify the power of genetics-based approaches in identifying novel genes that are putatively regulated by the AHR.